Breaking barriers: A study protocol on unveiling gender, racial and other intersectional dynamics in post-secondary institutions and identifying solutions for advancing primary care and public health research - Monica Aggarwal; Sabrina T. Wong; Andrea C. Tricco; Tanvir C. Turin; Aisha Lofters; Gina Agarwal; Barnini Bhattacharyya; Ivy Lynn Bourgeault (PLoS ONE, 2026)
Background and objectives This study protocol employs critical race and intersectionality theories to investigate barriers faced by racialized women at various academic career stages within Canadian primary care (PC) and public health (PH). The objectives are to identify faculty characteristics, examine intersectional barriers, and recommend equity-focused, inclusive strategies and policies. Research design and methods The study adopts a sequential mixed-methods approach. A quantitative survey and/or existing datasets will be used to collect demographic data on PC and PH academic position holders in Ontario and British Columbia, Canada. Data will also examine experiences of workplace discrimination; equity, diversity and inclusion (EDI) resource use; and departmental satisfaction. Subsequently, we will conduct interviews with researchers and leaders who are responsible for hiring and involved in or addressing matters related to EDI. Inductive and deductive approaches will be used to analyze the data in accordance with theoretical frameworks to deepen insights into equity and inclusion in academia. Results The quantitative phase will profile PC and PH academic position holders, highlighting disparities in positions and leadership roles. The qualitative study will explore intersectional challenges faced by racialized women academic position holders during career progression. Preliminary findings will inform effective equity-promoting strategies. Discussion and implications This study aims to contribute to the existing body of knowledge on gender and racial inequities in academia by uncovering systemic identity-based disparities in the careers of PC and PH researchers in Canada. The findings will inform the development of targeted interventions to promote equitable hiring, faculty support, and leadership advancement, enhancing diversity and productivity through an inclusive and equitable academic environment. Findings will be shared via publications, policy briefs, workshops, and online platforms to engage academics, advocacy groups, funders and policymakers in promoting equity and driving institutional change in PC and PH research.